Proud to Not Own Stocks: How Identity Shapes Financial Decisions - Henkel, Luca; Pugnaghi-Zimpelmann, Christian (Review of Financial Studies, 2026)
Abstract This paper introduces a key factor influencing households’ decision to invest in the stock market: how people view stockholders. Using surveys we conducted with nearly 8,500 individuals from 11 countries, we document that a large majority hold negative views of stockholders based on identity-relevant characteristics. Linking survey and administrative data, we find that negative perceptions strongly predict households’ stock market participation. We show that negative perceptions causally influence household decision-making and provide evidence supporting identity concerns as the underlying mechanism. Our findings provide new perspectives on the malleability of financial decision-making and a novel explanation for low stock market participation.